First record of Poltys nagpurensis (Araneae: Araneidae) from Iran - Alireza Zamani; Yuri M. Marusik; Mahmood Soofi; Seppo Koponen; John T. D. Caleb; Anna Šestáková (Germany, 2022)
A female specimen of Poltys (Araneidae) is reported from southern Iran, representing the first record of the genus for the whole Middle East and its westernmost record in the entire Asian region. The specimen was identified as Poltys nagpurensis Tikader, 1982, previously known only from central and western India. Since the Iranian specimen diﬀers in habitus morphology (but not in the epigyne), a brief description and comparison to the holotype with photos of the habitus and copulatory organs are provided.